Victims of crime in 22 European criminal justice systems : the implementation of recommendation (85) 11 of the Council of Europe on the position of the victim in the framework of criminal law and procedure : proefschrift - Brienen, Marion Eleonora Ingeborg; Hoegen, Ernestine (WLP, 2000)
Summary (s. 1-4).
Keywords: rikoslaki : Alankomaat; rikoslaki : Belgia; rikoslaki : Espanja; rikoslaki : Irlanti; rikoslaki : Islanti; rikoslaki : Iso-Britannia; rikoslaki : Italia; rikoslaki : Itävalta; rikoslaki : Kreikka; rikoslaki : Kypros; rikoslaki : Liechtenstein; rikoslaki : Luxemburg; rikoslaki : Malta; rikoslaki : Norja; rikoslaki : Portugali; rikoslaki : Ranska; rikoslaki : Ruotsi; rikoslaki : Saksan liittotasavalta; rikoslaki : Skotlanti; rikoslaki : Sveitsi; rikoslaki : Turkki; rikoslaki : Tanska; viktimologia : oikeusvertailu; rikoslaki : oikeusvertailu; rikosprosessi : oikeusvertailu